Beyond a Single World: Pedagogy and Relating in Difference - Mikulan, Petra (Paideusis, 2014)
The central notion of my analysis is that the relational values that are privileged by the feminine, if properly addressed in school, could foster a more inclusive and embodied way of addressing the fundamentally masculine origin of knowledge, curriculum planning as well as daily school rituals and cultures. For this reason I evoke the horizon of sense as captured by Irigaray in her two-ness of the world to designate a positive place for feminine subjectivity in the relational economy of the you and I, her and him. The economy of the placenta is evoked as a new form of connectedness enfolding a new kind of communication in a pedagogical interaction - where multiplicities and differences are privileged over sameness. ‘Touch’ is given primacy in the formation of a dialogue that does not appropriate but instead evokes the sharing of a desire in the two-ness of the world.